Ruthless trust : the ragamuffin's path to God - Manning, Brennan (San Francisco : HarperCollins, 2002)
"In his sequel to The Ragamuffin Gospel bestselling Christian author Brennan Manning shows us how true and radical trust in God can transform our lives."--P. [4] of cover.
Originally published in 2000.
Includes bibliographical references (p. 183-190).
Keywords: Trust in God -- Christianity; Christian life